Evaluation of a health and social care programme to improve outcomes following critical illness: a multicentre study. Issue 2 (21st March 2022) - Henderson, Philip; Quasim, Tara; Shaw, Martin; MacTavish, Pamela; Devine, Helen; Daniel, Malcolm; Nicolson, Fiona; O'Brien, Peter; Weir, Ashley; Strachan, Laura; Senior, Lorraine; Lucie, Phil; et al.
Abstract : Rationale: At present, clinicians aiming to support patients through the challenges after critical care have limited evidence to base interventions. Objectives: Evaluate a multicentre integrated health and social care intervention for critical care survivors. A process evaluation assessed factors influencing the programme implementation. Methods: This study evaluated the impact of the Intensive Care Syndrome: Promoting Independence and Return to Employment (InS:PIRE) programme. We compared patients who attended this programme with a usual care cohort from the same time period across nine hospital sites in Scotland. The primary outcome was health-related quality of life (HRQoL) measured via the EuroQol 5-dimension 5-level instrument, at 12 months post hospital discharge. Secondary outcome measures included self-efficacy, depression, anxiety and pain. Results: 137 patients who received the InS:PIRE intervention completed outcome measures at 12 months. In the usual care cohort, 115 patients completed the measures. The two cohorts had similar baseline demographics. After adjustment, there was a significant absolute increase in HRQoL in the intervention cohort in relation to the usual care cohort (0.12, 95% CI 0.04 to 0.20, p= 0.01). Patients in the InS:PIRE cohort also reported self-efficacy scores that were 7.7% higher (2.32 points higher, 95% CI 0.32 to 4.31, p =0.02), fewer symptoms of depression (OR 0.38, 95% CI 0.19 to 0.76, p=0.01) and similar symptoms of anxiety (OR 0.58, 95% CI 0.30 to 1.13, p =0.11). There was no significant difference in overall pain experience. Key facilitators for implementation were: integration with inpatient care, organisational engagement, flexibility to service inclusion; key barriers were: funding, staff availability and venue availability. Conclusions: This multicentre evaluation of a health and social care programme designed for survivors of critical illness appears to show benefit at 12 months following hospital discharge.